Equity and Prediction of Bed Allocation of the Department of Stomatology in Chinese Hospitals - Tan H (Dove Medical Press, 2024)
Hong Tan Department of Periodontal Mucosal Disease, The Affiliated Stomatology Hospital of Southwest Medical University, Oral & Maxillofacial Reconstruction and Regeneration of Luzhou Key Laboratory, Luzhou, Sichuan, 646000, People's Republic of ChinaCorrespondence: Hong Tan, Email tanhongcloud@126.comObjective: To analyze the equity of bed allocation of the department of stomatology in Chinese hospitals and predict the development in the next 5 years, so as to provide a scientific basis for promoting the development of oral health.Methods: Data on the beds of the department of stomatology in Chinese hospitals from 2017 to 2021 were obtained from the China Health Statistical Yearbook. The Gini coefficient, Lorenz curve, Theil index and agglomeration degree were used to analyze the equity of the bed allocation, and the grey prediction model GM(1,1) was used to predict the development from 2022 to 2026.Results: From 2017 to 2020, the Gini coefficient of bed allocation of the department of stomatology in Chinese hospitals was below 0.2 by population. From 2017 to 2021, the Gini coefficient of beds was above 0.6 by geography and between 0.2 and 0.3 by economy. The Theil index of beds ranged from 0.022 to 0.056 by population, from 0.532 to 0.564 by geography, and from 0.042 to 0.047 by economy. The inequity in the allocation by population was mainly from between regions, and the inequity in the allocation by geography and economy was mainly from within regions. Health resource agglomeration degree (HRAD) was greater than 2 in the eastern and central regions and less than 1 in the western region. HRAD/ population agglomeration degree (PAD) was greater than 1 in the northeast, eastern, and central regions and less than 1 in the western region. According to the prediction, the number of beds of the department of stomatology in Chinese hospitals will continue to increase, reaching 47,862.485 in 2026.Conclusion: The equity of bed allocation was better by population and economy than by geography. The equity of beds in the western region is insufficient equity by population and geography, and the equity of beds in the eastern region is insufficient equity by economy.Keywords: department of stomatology, beds, equity, prediction, China